Effective Use of Technology in Supervision Educational Institutions - Dewi Fatimah (CV. ADIBA AISHA AMIRA, 2022)
To achieve a quality learning system, first improve the quality of the teacher. In this case, it is the supervisor's job to provide guidance so that teachers can use technology according to their functions and follow technological developments so that they can advance and can achieve the goals set effectively. In increasing the productivity of education, educational institutions must develop according to the times, especially in the field of technology. Learning at these institutions needs to use a series of technological equipment that is able to work more effectively and efficiently according to the needs of the education itself. However, a supervisor must have competence in mastering new technology so that the implementation of supervision can be applied according to his competence